Financial Literacy for Business Sustainability: A Case of Lekhnath, Kaski, Nepal - Kandel, Upasana; Dhungana, Bharat Ram; Budhathoki, Dipika Sunar; Subedi, Chet Narayan; Acharya, Tara Nath (Journal of Development and Administrative Studies, 2025)
Business sustainability has become a big issue for entrepreneurs in developing countries like Nepal. Financial literacy empowers individuals and entrepreneurs in financing and investment decision-making, thereby developing a foundation for business sustainability. The research evaluates how financial literacy impacts small and medium enterprise (SME) sustainability at Lekhnath Kaski Nepal because business owners in this area lack essential financial management expertise which hinders their ability to run enterprises successfully over extended periods. Financial literacy represents a complex concept which includes financial planning and financing decision-making and investment decision-making and liquidity management and risk management and digital financial ability. The researchers applied a quantitative descriptive analytical research approach to gather primary data from 204 entrepreneurs through a structured questionnaire and stratified sampling method. The researchers used descriptive statistics and correlation analysis and multiple regression analysis to analyze the data. The study demonstrates that entrepreneurs possess moderate to high financial literacy skills but they excel in financial planning and liquidity management while their digital financial and risk management abilities remain less developed. The statistical analysis demonstrates that financial literacy increases business sustainability whereas investment decision-making ability serves as the most important factor for business sustainability. The results indicate that policymakers and institutions need to establish structured financial literacy programs together with digital finance training programs which will help SMEs in Nepal achieve better sustainability results.